2014
DOI: 10.1007/s11302-014-9431-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic and expression analysis of the adenosine signaling pathway members in Xenopus

Abstract: Adenosine is an endogenous molecule that regulates many physiological processes via the activation of four specific G-protein-coupled ADORA receptors. Extracellular adenosine may originate either from the hydrolysis of released ATP by the ectonucleotidases or from cellular exit via the equilibrative nucleoside transporters (SLC29A). Adenosine extracellular concentration is also regulated by its successive hydrolysis into uric acid by membrane-bound enzymes or by cell influx via the concentrative nucleoside tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…This muscle alteration was even more exacerbated by increasing the dose of MO, with severe reduction, and in some cases, absence of 12/101 positive domain and no somitic-like structure observed on the injected side in more than 80% of the injected 20 ng MO1 embryos (Figure 3C). This dose- gene encoding the Hypoxanthine-PhosphoRybosylTransferase (Hprt) in the salvage pathway (Figure 1A), the enzyme allowing metabolization of hypoxanthine, the major purine source in X. laevis embryos [46]. Comparable muscle alterations were obtained with independent knockdown of these genes, i.e.…”
Section: The Adsll Gene Is Required For X Laevis Myogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…This muscle alteration was even more exacerbated by increasing the dose of MO, with severe reduction, and in some cases, absence of 12/101 positive domain and no somitic-like structure observed on the injected side in more than 80% of the injected 20 ng MO1 embryos (Figure 3C). This dose- gene encoding the Hypoxanthine-PhosphoRybosylTransferase (Hprt) in the salvage pathway (Figure 1A), the enzyme allowing metabolization of hypoxanthine, the major purine source in X. laevis embryos [46]. Comparable muscle alterations were obtained with independent knockdown of these genes, i.e.…”
Section: The Adsll Gene Is Required For X Laevis Myogenesismentioning
confidence: 99%
“…However, from the early organogenesis phase (stage 22), all the 17 tested genes are expressed. We have previously shown that the unique reserve of purine in embryos, hypoxanthine, is depleted at stage 22 [46], so this embryonic stage is placed as a key turning point of purine source for the embryo. From this stage onwards and until stage 45 (stage where embryos start to feed), purines can only be synthesized de novo or recycled within the embryo, and zygotic expression of purine biosynthesis genes becomes then crucial.…”
Section: Role Of Purine Pathway Genes During X Laevis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…cDNA was synthesized from 1µg of RNA in 20µL final volume with Promega reverse transcriptase. Semi quantitative PCR was performed with the PCR primers listed in Table S1 and analysed on agarose gel as previously described (Tocco et al, 2015). Real time PCR was performed in a final volume of 20µL with the Mx3000P QPCR system (Stratagene-Agilent).…”
Section: Rna Extraction Rt-pcr and Real Time Pcr Analysismentioning
confidence: 99%
“…We have previously established the embryonic expression pattern of enpp and entpd ectonucleotidases and adenosine signaling pathway members in Xenopus embryos. The specific spatio-temporal expression profile of each member of ectonucleotidases and adenosine receptors, suggested that ATP, ADP and adenosine may have distinct and specific functions during vertebrate embryogenesis (Massé et al, 2006, 2010; Tocco et al, 2015). Indeed, we demonstrated that ADP, via the P2Y1 receptor, triggers eye development by regulating the expression of the eye field transcription factors, such as pax6 (Massé et al, 2007).…”
Section: Introductionmentioning
confidence: 99%